Polysulfone-based nanofiber and non-woven fabric
The SBS method produces polysulfone-based nanofibers with small diameters and low variation, forming nonwoven fabrics with high porosity and aperture ratios, addressing the limitations of phase separation methods and enhancing their industrial applicability in separation and adsorption processes.
Patent Information
- Application Number
- JP2024043972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-03-19
- Publication Date
- 2025-02-06
AI Technical Summary
Existing methods for producing porous materials with small pore sizes and high surface aperture ratios, such as those made by the phase separation method, struggle to achieve both high porosity and high surface opening ratios, limiting their effectiveness in separation and adsorption applications.
The use of the Solution Blow Spinning (SBS) method to produce polysulfone-based nanofibers with an average fiber diameter of 150 nm or less and a coefficient of variation of 0.5 or less, which are then accumulated to form nonwoven fabrics with a high surface aperture ratio and porosity, enhancing their separation and adsorption capabilities.
The resulting nanofibers and nonwoven fabrics exhibit excellent dissolution resistance and heat resistance, enabling their use in various industrial applications for separation and adsorption, including chemical, pharmaceutical, and environmental treatments.
Smart Images

Figure 2025018904000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to polysulfone nanofibers and nonwoven fabrics comprising the nanofibers. [Background technology]
[0002] Porous materials with small pore sizes (pores with sizes on the order of μm to nm) and high porosity and high surface opening rate are useful in various separation situations, such as filters for filtering gases and liquids, and as adsorbents or carriers for adsorbents. This is because, when separating specific components in fluids such as gases and liquids (for example, removing fine particles in gases and liquids, capturing valuable materials, etc.), it is desirable for the porous material used in the separation to be able to introduce a larger amount of the fluid to be separated into the material (i.e., the surface opening rate of the material surface and the porosity in the material are high) in terms of processing efficiency, and also because a small pore size makes it possible to incorporate the effect of sieving separation in the separation. Small pore sizes generally have a larger specific surface area, so they are more useful when used as adsorbents. The surface opening rate can also be said to be the porosity limited to the surface portion of the material. In this way, a "material with small pore sizes and high porosity and high surface opening rate" can be useful in various separation situations. Such "materials with small pore diameter and high porosity (high surface opening rate)" are generally often made by the "phase separation method" (for example, Non-Patent Document 1 below). However, with porous materials made by the phase separation method, although the porosity of the entire material can be high (for example, about 70%), the surface opening rate is not very high (for example, about 20%) (see Patent Document 1 below). This, that is, although the porosity of the entire material can be high, the surface opening rate cannot be very high, is presumably due to the fundamental constraints of the phase separation method.
[0003] There is another method for making porous materials, which is not the phase separation method in which a polymer solid precipitates from a liquid polymer solution and a porous skeletal structure is formed by the polymer solid at the same time as the polymer solid precipitates, but the method of "accumulating fibrous solids". The porous material made by this method (accumulation of fibrous solids) is a material called "nonwoven fabric" (see Non-Patent Document 2 below). In the manufacturing method of "accumulating solid materials called fibers from the beginning", unlike the "phase separation method" in which a polymer solid precipitates from a liquid polymer solution and a porous skeletal structure is formed by the polymer solid at the same time as the polymer solid precipitates, it is difficult to predict the reason why the porosity (surface opening rate because it is the surface of the material) is low (cannot be increased) especially on the surface of the material, and it is expected that it will be possible to create a material that has a high surface opening rate as well as a high porosity of the entire material (i.e., it is expected that the surface opening rate will be close to the porosity of the entire material). However, in the "fiber accumulation" method, the gaps between the fibers become "holes," so in order to achieve both a "small pore diameter" and a "high porosity (high surface opening rate)," "the fibers used for accumulation need to be thin."
[0004] "Thin fibers" (for example, fiber diameter of 1 μm or less) are called "nanofibers." Nanofibers are often produced by the electrospinning method (see Non-Patent Document 3 below). In recent years, research has been conducted on the solution blow spinning method (hereinafter also referred to as the SBS method), which is a method different from the electrospinning method, as a new nanofiber production technology (see Non-Patent Documents 4 and 5 below). Polysulfone-based polymers (polysulfone, polyethersulfone, etc.) are often used as porous materials such as membranes for sieving separation (see Non-Patent Document 1 below). This is thought to be because polysulfone-based polymers have excellent resistance to elution and heat, and therefore can be used in a wide range of applications, and are also easy to process, as they can be dissolved in a solvent and molded into various shapes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2001 / 053213 [Non-patent literature]
[0006] [Non-Patent Document 1] Noboru Kubota, Membrane, Vol. 33, pp. 239-246, 2008 [Non-Patent Document 2] "Technical Innovation and Market Outlook for Nonwoven Fabrics", Osaka Chemical Marketing Center, 2010 [Non-Patent Document 3] Hidetoshi Matsumoto, Membrane, Vol. 35, pp. 113-118, 2010 [Non-Patent Document 4] Medeiros, ES et al., J. Appl. Poly. Sci., 113 (2009) 2322-2330 [Non-Patent Document 5] J.Song et al., ACS Appl. Mater. Interfaces, 12 (2020) 33447-33464 Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above-mentioned state of the art, the problem to be solved by the present invention is to provide nanofibers composed of a polysulfone-based material, and a porous nonwoven fabric composed of the nanofibers, which has a small pore size, high porosity, and high surface opening rate. [Means for solving the problem]
[0008] The present inventors conducted intensive research and repeated experiments in order to solve the above problems, and unexpectedly discovered that by applying the SBS method, rather than the electrospinning method, to polysulfone-based fibers, it was possible to produce nanofibers with small diameters that had not been possible to obtain conventionally, as well as nonwoven fabrics composed of the nanofibers and having desired properties, which led to the completion of the present invention. That is, the present invention is as follows. [1] Fibers made of polysulfone-based materials with an average fiber diameter of 150 nm or less. [2] The fiber according to [1] above, having an average fiber diameter of 100 nm or less. [3] The fiber according to [1] above, having a coefficient of variation (σ / x), which is the ratio of the average fiber diameter (x) to the standard deviation (σ) of the average fiber diameter, of 0.5 or less. [4] The fiber according to [3], wherein the coefficient of variation (σ / x) is 0.3 or less. [5] The fiber according to [2] above, having a coefficient of variation (σ / x), which is the ratio of the average fiber diameter (x) to the standard deviation (σ) of the average fiber diameter, of 0.5 or less. [6] The fiber according to [5], wherein the coefficient of variation (σ / x) is 0.3 or less. [7] A nonwoven fabric composed of the fiber according to any one of [1] to [6] above, having a mean flow pore size of 0.6 μm or less, a porosity of 70% or more, and a surface opening rate of 60% or more. [8] A composite nonwoven fabric in which a layer composed of the fiber according to any one of [1] to [6] above is laminated on a nonwoven fabric support composed of fibers having an average fiber diameter of 1 μm or more, the composite nonwoven fabric having a mean flow pore size of 0.6 μm or less, a porosity of 70% or more, and a surface opening ratio of the layer composed of the fiber according to any one of [1] to [6] above being 60% or more. Effect of the Invention
[0009] According to the present invention, it is possible to obtain nanofibers made of a polysulfone-based material, and nonwoven fabrics made of the nanofibers, which have small pore diameters and high porosity and surface opening ratio. The nanofibers and nonwoven fabrics of the present invention have excellent resistance to elution and heat resistance, and therefore can be used in a wide range of applications, and can be suitably used in a wide range of industrial fields, such as the separation of various fluids (liquids and gases) in the chemical industry, pharmaceutical industry, water and sewage treatment, air purification treatment, etc. [Brief description of the drawings]
[0010] [Figure 1]Conceptual diagram of fiber production using the SBS method. (a) An example in which the gas flow pipe and the polymer solution pipe are separated, and (b) an example in which the gas flow pipe contains the polymer solution pipe. [Diagram 2] FIG. 1 is a conceptual diagram of fiber production by the SBS method carried out in Examples 1 to 7. [Diagram 3] 1 shows scanning electron microscope images of the fibers made of polyethersulfone obtained in Example 1. (a) Before pressing, (b) After pressing. [Figure 4] FIG. 1 is a model diagram for considering the relationship between fiber diameter and porosity (surface opening rate) (when the pore diameter is 1 times the fiber diameter). [Diagram 5] FIG. 1 is a model diagram for considering the relationship between fiber diameter and porosity (surface opening rate) (when the pore diameter is five times the fiber diameter). [Figure 6] 1 shows scanning electron microscope images of the composite nonwoven fabric obtained in Example 8. (a) is the surface on the polyethersulfone fiber laminate side, and (b) is a cross section of the composite nonwoven fabric. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the mode for carrying out the present invention (hereinafter also referred to as the present embodiment) will be described in detail. Note that the present invention is not limited to the embodiment described below, and can be used in various modifications within the scope indicated. One embodiment of the present invention is a fiber made of a polysulfone-based material and having an average fiber diameter of 150 nm or less.
[0012] <Polysulfone-based materials> Polysulfone is a polymeric compound that is also written as polysulfone, polysulfone, or polysulfone. Polysulfone-based materials include polysulfone (PSF), polyethersulfone (PES), and polyphenylsulfone (PPSU), and the chemical structure of the repeating unit is as follows:
[0013] [ka]
[0014] Polysulfone-based materials are amorphous materials that are used in a variety of materials, including porous membranes for sieving separation, due to their excellent heat resistance, resistance to elution, and chemical stability. The glass transition temperatures of polysulfone-based materials are 190°C for polysulfone, 225°C for polyethersulfone, and 220°C for polyphenylenesulfone. PSF, PES, and PPSU all have excellent heat resistance and resistance to elution, with PES being particularly superior.
[0015] <Average fiber diameter> The average fiber diameter is the average value of fiber diameters. When the distribution of fiber diameters is close to monodispersion and the standard deviation is sufficiently smaller than the average value, the average fiber diameter determines the properties of the nonwoven fabric, which is an accumulation of fibers. In particular, the separation performance of the nonwoven fabric, which is an accumulation of fibers, is greatly affected by the average fiber diameter and standard deviation, so the average fiber diameter is an important parameter in this embodiment.
[0016] The mainstream method for measuring fiber diameter is to use image analysis software to measure fiber diameters at multiple points on an electron microscope image (SEM image) of the fiber and then calculate the distribution, but there are also other measurement methods that utilize laser diffraction and air permeability. In this embodiment, the fiber diameter was measured at 50 points per sample from an electron microscope image (SEM image) using image analysis software (ImageJ, NIH) to obtain the average fiber diameter. The magnification of the SEM image used for the measurement is appropriately about 20,000 to 30,000 times if the fiber diameter is, for example, about 100 nm.
[0017] The smaller the average fiber diameter, the larger the specific surface area can be. Increasing the specific surface area increases the usefulness of the material when used as an adsorbent, etc. In addition, when fibers are accumulated to form a nonwoven porous material, a small average fiber diameter is preferable when making a "porous material with small pore diameter and high porosity (high surface opening rate)" that is useful in various separation situations. For example, when making a porous material with a pore diameter of 1 μm, the gaps between the fibers become pores, so if we assume that the fibers are dispersed into single fibers (for example, a two-dimensional projection type model in which fibers dispersed into single fibers (shaded areas) are arranged in a lattice pattern as shown in Figures 4 and 5), when it is made by accumulating fibers with a fiber diameter of 1 μm, the porosity (surface opening rate) is calculated to be 25% (equivalent to the case of Figure 4, (1a) 2 ÷(2a) 2 × 100 = 25%), and when made by accumulating fibers with a fiber diameter of 0.2 μm, the porosity (surface opening rate) can be calculated to be 69% (for example, corresponding to the case of Figure 5, (5a) 2 ÷(6a) 2 ×100=69%).
[0018] In this embodiment, the average fiber diameter is 150 nm (0.150 μm) or less, and preferably 100 nm (0.100 μm) or less. On the other hand, from the viewpoint of handling as a fiber, the average fiber diameter is preferably 20 nm or more. As shown in FIG. 5, when the average fiber diameter is 150 nm or less, the specific surface area can be made large, and when the fibers are accumulated to make a nonwoven porous material, it is possible to make a porous material with small pore diameter and high porosity (high surface opening rate) (for example, a pore diameter of 0.75 μm and a calculated porosity (surface opening rate) of 69%). When the average fiber diameter is 100 nm, the specific surface area can be made even larger, and for example, a pore diameter of 0.50 μm and a calculated porosity (surface opening rate) of 69%. Currently, porous materials with pores (small pore diameters) on the order of μm to nm are often made by the "phase separation method." Considering that it is difficult to achieve a surface opening rate of more than 30% using this phase separation method, fibers with an average fiber diameter of 150 nm or less (more preferably 100 nm or less) are preferable as substances that constitute "small pore diameter high porosity (high surface opening rate) materials." In addition, the surface opening rate of a porous material produced by the "phase separation method" is lower than the porosity of the entire material, but the surface opening rate of a porous material produced by the "fiber accumulation" technique can be made close to the porosity of the entire material.
[0019] <Coefficient of variation in fiber diameter> The coefficient of variation is the standard deviation divided by the average value. The coefficient of variation in fiber diameter can be defined as the ratio (σ / x) of the average fiber diameter (x) to the standard deviation (σ) of the average fiber diameter. In order to obtain reliable values for the average fiber diameter and standard deviation, the number of fiber diameter measurements is preferably several tens (approximately 50) or more. The smaller the coefficient of variation (σ / x) in fiber diameter, the smaller the variation in fiber diameter of the group of fibers. For example, when creating a "small pore diameter high porosity (high opening ratio) material" by accumulating fibers, this leads to a small variation in the "pore diameter" and "porosity (surface opening ratio)" formed by the gaps between fibers. Therefore, for example, when creating a "small pore diameter high porosity (high opening ratio) material" by accumulating fibers, it is important that the coefficient of variation (σ / x) in fiber diameter is small. The coefficient of variation (σ / x) in fiber diameter is preferably 0.5 or less, more preferably 0.3 or less.
[0020] Another embodiment of the present invention is a nonwoven fabric made of the above fibers, having a mean flow pore size of 0.6 μm or less, a porosity of 70% or more, and a surface opening ratio of 60% or more.
[0021] <Average flow pore diameter> The mean flow pore size is an index that expresses the pore size of a nonwoven fabric, taking into account the existence of a pore size distribution. When a fluid (gas or liquid) passes through a porous material with a pore size distribution, the amount of fluid passing through each pore in the nonwoven fabric is accumulated in order from the smallest pore size, and the pore size of the pore where the accumulated value reaches half (50%) of the amount of fluid passing through all pores is the mean flow pore size. Since nonwoven fabrics are often used for fluid (gas or liquid) permeation applications, the "mean flow pore size" is an index of pore size that is often used as a practical way of expressing pore size. An example of a measurement method is the bubble point method. In this method, a porous membrane is immersed in a liquid with a known surface tension, and a weak air pressure is applied while all the internal pores are filled with liquid. When the air pressure is increased, the air passes through at the moment when the air pressure exceeds the surface tension of the liquid, and the pore size at this time can be calculated using the following formula.
[0022]
number
[0023] In the formula, D is the pore size, γ is the surface tension, θ is the contact angle of the liquid, and P is the air pressure; if the air pressure is further increased from this point, air will penetrate through other pores as well, and eventually all pores will be penetrated. The increase in air flow rate at a certain point indicates the proportion of pore sizes where the surface tension is equal to the pressure at that time, so by comparing this with the amount of air that penetrates before immersion in liquid, the pore size distribution can be determined. The diameter at the moment when the flow rate of transmitted air reaches 50% of the total flow rate is the average flow pore size.
[0024] In this embodiment, the mean flow pore size was determined by the bubble point method using a perm porometer (CFP-1200AEX, PMI) and Galwick test liquid (surface tension 15.9 dyne / cm). Porous materials with a pore size of 1 μm or less are often produced by the "phase separation method". However, although the porosity of the entire material can be increased, it is difficult to increase the surface opening rate (porosity of the material surface) of porous materials produced by the "phase separation method". On the other hand, by using the SBS method, for example, for porous materials with a pore size of 1 μm or less that are currently often produced by the "phase separation method", that is, by producing a nonwoven fabric by accumulating fibers that can increase not only the porosity of the entire material but also the porosity (surface opening rate) of the material surface, it is possible to obtain a "material with a small pore size (for example, 1 μm or less) and high porosity (high surface opening rate)" that is useful in various separation processes and the like. The mean flow pore size of the nonwoven fabric of this embodiment is 0.6 μm or less.
[0025] <Porosity and surface opening rate> The porosity and surface opening rate indicate the ratio of voids present inside and on the surface of a porous material, respectively. These affect the fluid permeability inside the material and on the surface, respectively. In the manufacturing process of porous materials made by phase separation, the surface opening rate is significantly lower than the porosity, whereas in nonwoven fabrics made of accumulated fibers, the surface opening rate and porosity are close to each other, allowing the material to maintain high permeability.
[0026] The porosity of the nonwoven fabric of this embodiment can be calculated by dividing the weight of the nonwoven fabric by its volume to obtain an apparent density, as shown in the following formula, and comparing this with the true density of the material constituting the porous material (actual measurements or literature values can be used). For example, for a circular nonwoven sample, if W is the weight of the nonwoven sample, r is the radius of the nonwoven sample, and d is the thickness of the nonwoven sample, then the apparent density of the membrane is ρ apa If the true density of the material that constitutes the porous material is ρ0, the porosity ε can be calculated. For example, the true density of polyethersulfone, which is one of the polysulfone-based materials, is 1.37 g / cm 3 It is.
[0027]
number
[0028]
number
[0029] The surface porosity can be calculated from the area ratio of the non-fiber parts by binarizing the SEM image of the porous material surface into black and white using image analysis software. The appropriate magnification of the SEM image is several thousand to several tens of thousands when the pore size (interfiber gap) is about 1 μm to 0.1 μm. When separating specific components from a fluid such as gas or liquid (for example, removing fine particles from a gas or liquid, capturing valuable materials, etc.), it is desirable for the porous material used for separation to be able to introduce a large amount of the fluid to be separated into the material in terms of processing efficiency. From this perspective, it is desirable for the surface opening rate of the material surface and the material (the entire material) to be high. However, if the porosity is too high, the strength of the material will be weakened and problems will occur. The porosity and surface opening rate of the nonwoven fabric of this embodiment are preferably 70% or more and 95% or less and 60% or more and 95% or less, respectively, and more preferably 75% or more and 90% or less and 70% or more and 90% or less, respectively.
[0030] <Examples of fiber manufacturing methods> (Solution Blow Spinning method) The nanofibers made of the polysulfone-based material of this embodiment can be produced, for example, by the "Solution Blow Spinning method (SBS method)". The SBS method is a technical technique in which a polymer solution in which a polymer compound is dissolved in a solvent is discharged from a hollow capillary such as a syringe needle, and a strong gas flow (e.g., compressed air) is applied to the polymer solution discharged from the tip of the hollow capillary to stretch the polymer solution thinly and collect it in a collector installed at a position (e.g., several tens of centimeters to 1 meter) slightly away from the tip of the hollow capillary. The solvent of the polymer solution evaporates between the tip of the hollow capillary and the collector, and the fibrous polymer solid (fiber) from which the solvent has evaporate is accumulated in the collector. Figure 1 shows an example of a conceptual diagram of fiber production by the SBS method. Note that Figure 1(a) is an example of a conceptual diagram of fiber production when the gas flow pipe and the polymer solution pipe are separated, and Figure 1(b) is an example of a conceptual diagram of fiber production in which the gas flow pipe contains the polymer solution pipe.
[0031] Unlike the electrospinning method, which has been widely used in the past as a method for producing nanofibers, the SBS method does not require the use of high voltage, has no restrictions on the conductivity of the polymer solution used, and is a method that can increase the fiber production rate (productivity), making it a technical method suitable for industrial use. This is thought to be based on the difference in the principle of stretching the polymer solution between the two methods, in that in the process of "creating thin fibers by stretching the polymer solution while volatilizing the solvent," the "stretching of the polymer solution into a thin shape" is done by "applying an electric field to the polymer solution and using the potential difference as the driving force," whereas in the SBS method, "stretching of the polymer solution by applying a gas flow (high-pressure air, etc.) to the polymer solution" is done.
[0032] (polymer solution) The polymer solution can be prepared by dissolving the polysulfone polymer compound in a solvent. The solvent is not particularly limited as long as it dissolves the polysulfone polymer compound, but dimethylacetamide (DMAC), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), etc. can be used alone or in combination (mixed). In addition, poor solvents for polysulfone polymer compounds and various additives can be added to the polymer solution within a range that does not impair the solubility of the polysulfone polymer compound. Examples of poor solvents and various additives for polysulfone polymer compounds include ethylene glycol compounds such as tetraethylene glycol, low boiling point compounds such as acetone, polyethylene glycol compounds of various molecular weights (several hundred to several hundred thousand), and polyvinylpyrrolidone compounds of various molecular weights (several hundred to several hundred thousand). These poor solvents and various additives for polysulfone polymer compounds can be used as adjusters for the volatility and viscosity of the polymer solution.
[0033] If the concentration of the polysulfone polymer compound is too low, it will tend to be particulate rather than fibrous, and if the concentration is too high, it will be difficult to form thin fibers. For example, if the molecular weight is about 50,000 to 100,000, the concentration of the polysulfone polymer compound is preferably 20% by weight to 40% by weight, more preferably 25% by weight to 35% by weight.
[0034] (Nozzle (spinning nozzle)) The hollow capillary that discharges the polymer solution is generally called a "nozzle (spinning nozzle)." There are no particular limitations on the type of nozzle, as long as the polymer solution can be stretched by contacting it with a gas flow (compressed air, etc.) at the tip of the hollow capillary (nozzle tip) from which the polymer solution is discharged. Examples of the nozzle include the type shown in Figure 1(a) and the type shown in Figure 1(b).
[0035] Figure 1(a) shows a case where the gas flow pipe and the polymer solution pipe (hollow capillary) are separated. For example, a syringe needle bent at a right angle near the polymer solution discharge part so that the discharged polymer solution is parallel to the gas flow (compressed air, etc.) can be used as the hollow capillary through which the polymer solution flows. From the viewpoint of safety, air can typically be used as the gas flow (compressed air). For example, by connecting a pipe from a compressor to the hollow capillary through which the polymer solution is discharged, compressed air can be applied to the discharged polymer solution near the tip of the hollow capillary through which the polymer solution is discharged, thereby stretching the discharged polymer solution.
[0036] Figure 1(b) shows a case where the gas flow pipe contains a polymer solution pipe (hollow capillary). In this case, the polymer solution discharged from the hollow capillary tends to be discharged stably in parallel with the flow direction of the gas flow, making it easy to stably stretch the polymer solution. From the viewpoint of safety, air can typically be used as the gas flow (compressed air). For example, the polymer solution can be stretched by connecting a pipe from a compressor to the gas pipe containing the hollow capillary.
[0037] In the SBS method, the principle of making thin fibers is to "stretch the discharged polymer solution thinly by putting it on a gas flow (compressed air, etc.)," so it is desirable that the hollow capillary that serves as the flow path for the polymer solution is thin, at least near the discharge part (tip). However, if it is too thin, the pressure loss for the flow of the polymer solution will be large, and there will be a risk of the capillary being blocked by a small amount of foreign matter (such as a gel-like substance remaining after dissolving the polymer compound), so this is not desirable. The diameter (inner diameter of the hollow part) of the hollow capillary that serves as the path for the polymer solution is preferably 0.1 mm or more and 0.5 mm or less.
[0038] (Polymer solution ejection conditions) In the SBS method, the principle of creating thin fibers is to "stretch the discharged polymer solution thinly by putting it on a gas flow (compressed air, etc.)," so the "discharge flow rate (flow rate per hour) from the nozzle (hollow capillary) of the polymer solution" and the "strength of the gas flow (gas pressure) at the polymer solution discharge part" are important conditions when discharging the polymer solution. The stronger the gas flow (gas pressure) at the polymer solution discharge part (the higher the gas pressure), the thinner the obtained fiber will be, but the discharge flow rate of the polymer solution must be at least to a certain level to make a stable fiber (spinning cannot be stably performed). Therefore, the absolute values of the discharge flow rate of the polymer solution and the strength of the gas flow (gas pressure) at the polymer solution discharge part are important, but the balance between the two is also important. In addition, from the viewpoint of productivity in industrial practical use, it is preferable that the flow rate of the polymer solution discharge part is high. From the above viewpoints, the gas pressure at the polymer solution discharge section and the discharge flow rate of the polymer solution are preferably from 0.01 MPa to 0.3 MPa and from 0.1 mL / h to 20 mL / h, respectively, and more preferably from 0.02 MPa to 0.2 MPa and from 0.5 mL / h to 10 mL / h. The process can be carried out at room temperature (approximately 10 to 30° C.). Taking into consideration the volatility, stability, and solidification property of the polymer solution, the process can also be carried out at a temperature away from room temperature.
[0039] Since polysulfone-based materials have a certain degree of hydrophobicity, polymer solutions in which polysulfone-based polymer compounds are dissolved may cause solid precipitation (coagulation) if they absorb a large amount of moisture. If the polymer solution absorbs moisture (humidity) from the environment at the discharge part during discharge of the polymer solution, causing solid precipitation, clogging at the tip of the hollow capillary is likely to occur. Therefore, it is preferable to keep the humidity at least near the polymer solution discharge part low (relative humidity 40% or less, more preferably 30% or less).
[0040] (Distance from discharge to collector) The distance from the polymer solution discharge part (the tip of the hollow capillary) to the collector is where the solvent is evaporated from the stretched polymer solution, turning the stretched polymer solution into a "thin fibrous solid". Therefore, the distance must be long enough to evaporate most of the solvent used and solidify the polymer solution. On the other hand, if the distance is too long, the thin fibrous solids produced by the solvent evaporation will scatter, resulting in a large amount of fibrous solids that cannot be collected in the collector, which is undesirable. The appropriate distance varies depending on the volatility of the solvent and the ambient temperature, but for example, when the solvent is DMAC and the ambient temperature is room temperature, it is about 30 cm to 200 cm. If it is desired to promote the evaporation of the solvent, the environmental temperature can be increased and / or a radiant heat source such as an infrared lamp can be installed near the polymer solution outlet (the tip of the hollow capillary). Conversely, if it is desired to produce fibers while suppressing the evaporation of the solvent, the environmental temperature can be lowered.
[0041] (collector) The collector is a place where the polymer solid matter that flies in as fibrous solid matter due to the evaporation of most of the solvent from the polymer solution discharged from the tip of the hollow capillary and stretched by the gas flow is collected. In order to collect the fibrous solid matter that flies in on the gas flow, the collector must have a structure that allows the gas flow that hits the collector to escape outside while collecting the fibrous solid matter. Therefore, the basic structure of the collector is preferably a mesh sheet or cage structure. For example, a cylindrical or rectangular cage with a mesh-like bottom and side surfaces partially or entirely and an open top, a sheet-like object partially or entirely mesh-like, etc. can be used as the collector.
[0042] The material of the collector is not particularly limited, but since the fibrous polymer solid matter may contain a small amount of solvent when it reaches the collector, a material that is resistant to the solvent used (DMAC, DMF, NMP, etc.) and has a certain degree of mechanical strength to maintain the structure is preferable. Specifically, metals such as stainless steel, fluororesins such as polytetrafluoroethylene, and resins such as polyethylene and polypropylene can be used. It is preferable that the fibrous polymer solid matter collected in the collector can be smoothly removed from the collector. From this viewpoint, fluororesins such as polytetrafluoroethylene, which have low adhesion to polysulfone-based materials (easy demolding), are preferable. In order to improve compatibility between the structural maintenance (strength of the structure) of the collector and the releasability of the fibrous polymeric solid material made of a polysulfone-based material, a cage collector with a double structure can be used, in which a resin mesh cage made of, for example, polytetrafluoroethylene resin is placed inside a cage made of a metal mesh.
[0043] The mesh openings of the collector are preferably about 1 mm to 10 mm square so that the gas flow can escape (pass through) while collecting the fibrous polymeric solid matter. In order to collect the fibrous solid matter while allowing the gas flow to escape to the outside of the collector more reliably, the gas flow can be sucked from the back of the collector using a suction blower or the like. In order to more reliably remove fibrous solid matter composed of polysulfone-based materials collected on a collector from the collector without causing damage, even if a fluororesin such as polytetrafluoroethylene, which has excellent release properties, is used as the collector material, the fibrous solid matter can be removed by blowing air from an electrostatic removal blower (a blower that has both corona discharge and air blowing functions) onto the back of the collector.
[0044] <Nonwoven fabric manufacturing method example> The fibrous solid matter composed of polysulfone-based material collected in the collector is often in the form of a lump or a sheet having an uneven thickness. When used for separation processing of various fluids (liquids, gases), it is often preferable for the solid matter to be in the form of a sheet (nonwoven fabric) having a uniform thickness (such as when the fluid to be processed (liquid, gas) is passed through the sheet for filtration separation or adsorption separation). Of course, when used for adsorption separation, there are many cases where it is acceptable for the solid matter to be in the form of a lump or a sheet having an uneven thickness, and in this case, there is no particular need to form the solid matter into a sheet as described below.
[0045] Hereinafter, we will describe a method for forming fibrous solid matter composed of polysulfone-based material collected in a collector (which is often in the form of lumps or sheets of uneven thickness) into a sheet of relatively uniform thickness (nonwoven fabric) after removing it from the collector. The fibrous solid material removed from the collector can be made into a sheet (nonwoven fabric) of relatively uniform thickness by pressing. Pressing is an operation in which the fibrous solid material is placed on a flat plate and then sandwiched between another flat plate in a parallel positional relationship with the first plate under pressure. The main operating factors in pressing are (i) pressure, (ii) temperature, and (iii) time. The thickness is mainly determined by the pressure.
[0046] Before the press treatment, if any solvent (DMAC, DMF, NMP, etc.) used in fiber production remains in the fibrous solid, it is preferable to completely remove it. The solvent can be removed by placing it in a temperature range of room temperature to the glass transition temperature of 50°C or less, preferably under reduced pressure, for about several hours. The glass transition temperatures of polysulfone-based materials are 190°C for polysulfone, 225°C for polyethersulfone, and 220°C for polyphenylenesulfone, and the boiling points of the solvents are 165°C for DMAC, 153°C for DMF, and 202°C for NMP under atmospheric pressure.
[0047] As a preferred operating condition, the pressure is, for example, 0.02 to 0.15 MPa if the thickness after sheeting (after nonwoven fabric) is 100 μm to 200 μm. If a thicker thickness is desired, a lower pressure is used appropriately, and if a thinner thickness is desired, a higher pressure is used appropriately. The temperature can be within a range from room temperature to 10° C. below the glass transition temperature. If the press treatment is performed at a temperature close to the glass transition temperature (for example, 10 to 50° C. below the glass transition temperature), the fibers can be weakly adhered and bonded at the fiber entanglement portion, which is preferable in terms of maintaining the fiber structure in the obtained sheet (nonwoven fabric). In addition, the temperature can be changed gradually from a low temperature to a high temperature, rather than being limited to one temperature, or a press treatment can be performed at a low temperature and then at a high temperature. The time can be about several minutes to about one hour. One preferred example is a method in which, from the viewpoint of not unnecessarily disturbing the fiber structure, a press treatment is performed at a low temperature (near room temperature) at 0.02 to 0.15 MPa for about 10 minutes, and then a press treatment is performed at the same pressure and at a temperature near the glass transition temperature (for example, 10 to 50°C below the glass transition temperature) for about 10 minutes.
[0048] (Composite nonwoven fabric) A layer (nonwoven sheet-like layer) made of nanofibers composed of the polysulfone-based material of this embodiment can also be laminated on another nonwoven sheet having a larger (thicker) average fiber diameter to form a composite nonwoven fabric. A nonwoven fabric sheet with a larger (thicker) average fiber diameter has great mechanical strength, so by using a nonwoven fabric sheet with a larger (thicker) average fiber diameter as a support and laminating a layer (nonwoven fabric sheet-like layer) made of nanofibers with a smaller average fiber diameter made of the polysulfone-based material of this embodiment on top of it to form a composite nonwoven fabric, it is possible to obtain a nonwoven fabric made of nanofibers made of the polysulfone-based material of this embodiment, which has superior mechanical strength. The nonwoven fabric sheet used as the support is used to reinforce the mechanical strength of the layer (nonwoven fabric sheet-like layer) composed of nanofibers made of the polysulfone-based material of this embodiment, and therefore preferably satisfies the following requirements: (A) Average fiber diameter: From the viewpoint of mechanical strength reinforcement, the larger (thicker) the better, but from the viewpoint of bonding (adhesion) with the nanofibers, it is preferable that the diameter is not too large (not too thick) so as to increase the bonding density with the nanofibers. From the above viewpoints, the average fiber diameter is preferably 1 μm or more and 50 μm or less, more preferably 3 μm or more and 30 μm or less. (B) Porosity: 70% or more is preferable so that the "high (large) porosity" that is a feature of the layer (nonwoven sheet) composed of nanofibers is not excessively reduced as a whole composite nonwoven fabric after compounding. On the other hand, if the porosity is too high, the density of the junctions with the nanofibers becomes small, so 95% or less is preferable. (C) Material: From the viewpoint of ensuring the bondability with nanofibers made of polysulfone-based materials, it is preferable to be able to enhance the bondability with the polysulfone-based material by partial thermal fusion, etc., by heating treatment such as heat pressing, etc. From this viewpoint, materials with a glass transition temperature of 200°C or less are preferable so that thermal fusion with the polysulfone-based material is possible, and for example, polyethylene terephthalate (PET, glass transition temperature: about 77°C) and polyolefins (polypropylene, polyethylene, etc.) can be suitably used.
[0049] The composite nonwoven fabric can be produced, for example, by (a) placing a nonwoven fabric support inside a collector (such as by attaching it to the inner surface of the collector) and directly laminating a layer of nanofibers (a nonwoven fabric sheet-like layer) on the nonwoven fabric support, or (b) collecting nanofibers in a cotton-like form using a collector, removing the nanofibers, placing them on a separately prepared nonwoven fabric support, and then heat pressing as necessary. Even with the method (a), a composite nonwoven fabric that is smoother and has better bonding properties (bonding properties between the support nonwoven fabric and the nanofiber layer) can be obtained by heat pressing after laminating the nanofibers. The heat pressing method described above can be used.
[0050] <Application> Porous materials with small pore diameters (pores of the order of μm to nm) and high porosity and high surface opening ratios, such as nonwoven fabrics, are useful in various separation situations, such as filters for filtering gases and liquids, and as adsorbents or carriers for adsorbents. This is because, when separating specific components in fluids such as gases and liquids (for example, removing fine particles in gases and liquids, capturing valuable materials, etc.), it is desirable for the porous material used in the separation to be able to introduce a large amount of the fluid to be separated into the material (i.e., the surface opening ratio of the material surface and the porosity in the material are high) in terms of processing efficiency, and also because a small pore diameter makes it possible to incorporate the effect of sieving separation in the separation. In addition, a small pore diameter generally leads to a large specific surface area, so that the usefulness of the material as an adsorbent material is also increased. The surface opening ratio can also be said to be the porosity limited to the surface portion of the material. Thus, a material having a small pore size, high porosity, and high surface opening ratio can be useful in various separation situations.
[0051] Specifically, "materials having small pore sizes and high porosity and high surface opening ratio" can be used for air purification (screening and / or adsorption to prevent and remove harmful substances such as fine particles and viruses in the air), carriers of materials that support carbon dioxide adsorption functional substances such as amine compounds and inorganic particles (zeolite particles and MOF (Metal Organic Frameworks) particles) and recover carbon dioxide from exhaust gases or air, carriers of materials that support metal ion capture functional substances such as ion exchange groups and chelating groups and recover metal ions from liquids, liquid clarification (screening and / or adsorption to prevent and remove fine particles in water or organic liquids), recovery of valuable resources in liquids (collection of valuable cells and valuable fine particles in water, etc.), etc. EXAMPLES
[0052] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0053] Example 1 Polyethersulfone (PES) (BASF, grade: Ultrason E6020P) was used as the polysulfone material, and dimethylacetamide (DMAC) was used as the solvent to prepare a PES solution (polymer solution) in which PES was dissolved in DMAC at 30% by weight. This PES solution (polymer solution) was spun (fiber production) using the SBS method using the device shown in Figure 2. The PES solution (polymer solution) placed in the syringe was passed through the inside of the tube of a 27G injection needle (inner diameter 0.2 mm, outer diameter 0.4 mm, length 5 cm) by a syringe pump (manufactured by KD Scientific, grade name: KDS100 Legacy Single Syringe Infusion Pump) and discharged from the spinning nozzle. A gas flow (compressed air) was produced by an air compressor (manufactured by Anest Iwata, grade name: SLP-15EFD) (pressure 0.8 MPa), and after pressure adjustment by a pressure regulator through piping, it was introduced into the spinning nozzle and discharged from the spinning nozzle. The compressed air was discharged from a circular opening (27G injection needle is present at the center position of the opening) with a diameter of 0.8 mm of the spinning nozzle along the outer circumference of the 27G injection needle in the same direction as the PES solution (polymer solution) discharged from the 27G injection needle. The discharge rate of the PES solution (polymer solution) was 1.0 mL / h, the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) was 0.10 MPa, the environmental temperature was approximately 20 to 30°C, and the environmental humidity was approximately 20 to 30% relative humidity.
[0054] A cylindrical basket-shaped stainless steel mesh (3 mm square mesh) with a diameter of 14 cm and a length of 21 cm was used as the collector. A cylindrical basket-shaped Teflon (registered trademark) mesh (3 mm square mesh) was placed inside the cylindrical basket-shaped stainless steel mesh so that it was attached to the inside, forming a double-structure cylindrical basket-shaped mesh with a stainless steel mesh on the outside and a Teflon (registered trademark) mesh on the inside. The suction port of a suction blower (manufactured by Kyocera Corporation, grade name: ABL3500VDX) was placed on the bottom of the cylindrical basket-shaped collector, and spinning (fiber production) was performed while suctioning from the bottom of the collector. The distance from the discharge part of the spinning nozzle to the bottom of the collector was 60 cm.
[0055] After about 40 minutes of spinning, the discharge of the PES solution (polymer solution) was stopped, and spinning (fiber production) was terminated. A large amount of white fibers was deposited on the bottom and sides inside the collector. The Teflon (registered trademark) mesh part, which was the inner part of the cylindrical basket-shaped collector, was removed, and the fibers deposited on the mesh surface were removed (cotton-like) while blowing air from an electrostatic removal blower (manufactured by AS ONE Corporation, grade name: AS-18) from the opposite side (back side) of the deposition surface. The average fiber diameter of the obtained fibers was 76 nm, and the σ / x of the fiber diameter was 0.13. The removed fibers (cotton-like) were dried under reduced pressure at 170°C for 2 hours in order to completely remove DMAC. The cotton-like fibers were then placed on a Teflon (registered trademark) sheet in an area of about 10 cm square and set on the press surface of a small heat press (H300-01, manufactured by AS ONE). After setting, the fibers were pressed at room temperature (25°C) for 10 minutes at a pressure of 0.07 MPa, and then pressed at 200°C for 10 minutes at a pressure of 0.07 MPa to obtain a sheet-like material (nonwoven fabric-like material).
[0056] A circular sample with a diameter of 2 cm was cut out from the obtained sheet (nonwoven fabric), and various properties of the nonwoven fabric were measured. The average fiber diameter was 81 nm, the fiber diameter σ / x was 0.22, the mean flow pore size was 0.30 μm, the porosity was 85%, the surface opening ratio was 71%, the thickness was 150 μm, and the basis weight was approximately 30 g / m 2 It was.
[0057] (Reference example 1) Using a self-made device, spinning (fiber production) was performed by electrospinning (electrospinning method). The same PES solution (polymer solution) as in Example 1 placed in a syringe was passed through the inside of a 27G injection needle (inner diameter 0.2 mm, outer diameter 0.4 mm, length 1.5 cm) by a syringe pump (Minato Concept, grade name: MCIP-III) and discharged from a spinning nozzle. When a DC voltage of 12 kV was applied between the nozzle and an aluminum plate (area 7 cm x 7 cm) placed 12 cm away from the nozzle tip using a DC high-voltage stabilized power supply (Matsusada Precision, grade name: HAR100P0.3), the polymer solution was continuously discharged due to electrostatic repulsion caused by the charge of the polymer solution (polarity on the nozzle side is positive). The discharge rate of the PES solution (polymer solution) was 0.2 mL / h, the nozzle-collector distance was 12 cm, the environmental temperature was approximately 20 to 30°C, and the environmental humidity was approximately 20 to 30% relative humidity. After about 70 minutes of spinning, the application of voltage and the discharge of the PES solution (polymer solution) were stopped, and spinning (fiber production) was terminated. The fibers were deposited in a sheet-like layer on the aluminum substrate. The average fiber diameter of the obtained fibers was 267 nm, and the fiber diameter σ / x was 0.24. A circular sample with a diameter of 2 cm was cut out from the obtained sheet-like deposit (nonwoven fabric deposit), and various properties as a nonwoven fabric were measured, resulting in an average flow pore size of 0.67 μm, a porosity of 85%, a surface opening rate of 80%, a thickness of approximately 45 μm, and a basis weight of approximately 9 g / m. 2 It was.
[0058] Example 2 Spinning (fiber production) was performed in the same manner as in Example 1, except that the discharge rate of the PES solution was 5.0 mL / h and the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) was 0.08 MPa. The average fiber diameter of the obtained fibers was 90 nm, and the σ / x of the fiber diameter was 0.38.
[0059] Example 3 Except for setting the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) to 0.06 MPa, spinning (fiber production) was performed in the same manner as in Example 2. The average fiber diameter of the obtained fibers was 100 nm, and the σ / x of the fiber diameter was 0.35.
[0060] Example 4 Except for setting the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) to 0.04 MPa, spinning (fiber production) was performed in the same manner as in Example 2. The average fiber diameter of the obtained fibers was 110 nm, and the σ / x of the fiber diameter was 0.36.
[0061] Example 5 Except for setting the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) to 0.02 MPa, spinning (fiber production) was performed in the same manner as in Example 2. The average fiber diameter of the obtained fibers was 130 nm, and the σ / x of the fiber diameter was 0.31.
[0062] Example 6 Except for setting the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) to 0.10 MPa, spinning (fiber production) was performed in the same manner as in Example 2. The average fiber diameter of the obtained fibers was 76 nm, and the σ / x of the fiber diameter was 0.14.
[0063] Example 7 Except for setting the pressure of the compressed air after pressure adjustment (measured at the introduction position into the spinning nozzle) to 0.06 MPa, spinning (fiber production) was performed in the same manner as in Example 1. The average fiber diameter of the obtained fibers was 125 nm, and the σ / x of the fiber diameter was 0.32. Further, a sheet-like material (nonwoven fabric) was obtained from the obtained fibers in the same manner as in Example 1. A circular sample having a diameter of 2 cm was cut out from the obtained sheet-like material (nonwoven fabric), and various property values as a nonwoven fabric were measured in the same manner as in Example 1. The average fiber diameter was 129 nm, the fiber diameter σ / x was 0.34, the mean flow pore size was 0.54 μm, the porosity was 71%, the surface opening ratio was 74.3%, the thickness was 420 μm, and the basis weight was about 170 g / m 2 It was.
[0064] Example 8 The fibers (cotton-like) collected in the collector in Example 1 were placed on a PET nonwoven fabric (Eltas E05012, manufactured by M.A. Materials, Inc., average fiber diameter 13 μm, porosity 89%) and heat-pressed using a small heat press machine (H300-01, manufactured by AS ONE) (temperature 200° C., pressure 0.28 MPa, time 10 minutes) to obtain a composite nonwoven fabric. In the obtained composite nonwoven fabric, the polyethersulfone nanofibers had an average fiber diameter of 100 nm, and the fiber diameter σ / x was 0.30. The composite nonwoven fabric as a whole had a mean flow pore size of 0.43 μm, a porosity of 85%, a surface opening ratio (on the nanofiber layer side) of 77%, a thickness of 69 nm, and a basis weight of about 14 g / m. 2 It was. [Industrial Applicability]
[0065] According to the present invention, it is possible to obtain nanofibers made of a polysulfone-based material, and nonwoven fabrics made of the nanofibers, which have small pore diameters and high porosity and surface opening ratio. The nanofibers and nonwoven fabrics of the present invention have excellent resistance to elution and heat resistance, and therefore can be used in a wide range of applications, and can be suitably used in a wide range of industrial fields, such as the separation of various fluids (liquids and gases) in the chemical industry, pharmaceutical industry, water and sewage treatment, air purification treatment, etc.
Claims
1. A fiber made of a polysulfone-based material with an average fiber diameter of 150 nm or less.
2. 2. The fiber of claim 1, having an average fiber diameter of 100 nm or less.
3. 2. The fiber according to claim 1, wherein the coefficient of variation (σ / x), which is the ratio of the average fiber diameter (x) to the standard deviation (σ) of the average fiber diameter, is 0.5 or less.
4. 4. The fiber according to claim 3, wherein the coefficient of variation (σ / x) is 0.3 or less.
5. 3. The fiber according to claim 2, wherein the coefficient of variation (σ / x), which is the ratio of the average fiber diameter (x) to the standard deviation (σ) of the average fiber diameter, is 0.5 or less.
6. 6. The fiber according to claim 5, wherein the coefficient of variation (σ / x) is 0.3 or less.
7. A nonwoven fabric comprising the fibers according to any one of claims 1 to 6, having a mean flow pore size of 0.6 µm or less, a porosity of 70% or more, and a surface opening ratio of 60% or more.
8. A composite nonwoven fabric comprising a layer composed of the fiber according to any one of claims 1 to 6 laminated on a nonwoven fabric support composed of fibers having an average fiber diameter of 1 μm or more, the composite nonwoven fabric having a mean flow pore size of 0.6 μm or less, a porosity of 70% or more, and a surface opening ratio of the layer composed of the fiber according to any one of claims 1 to 6 being 60% or more.
Citation Information
Patent Citations
Method for purifying suspended water by membrane filtration
WO2001053213A1